Heritage Studies in Architectural Education. Case of Ukraine at Time of War (EAAE Annual Conference Proceedings, 2023)
The materiality of architecture, however, forms an intangible heritage that becomes an integral part of the tangible heritage. The destruction of Ukrainian cities due to war raises the question of the destruction of collective memory, which in turn encourages reflection on heritage and memory in general. Considering physical destruction along with the destruction of paradigms caused by war and anticipating the upcoming post-war restoration of Ukrainian cities, a necessity for the rethinking of approaches and focuses in architectural education comes to light. A discussion on the contradictory topic of the multiplicity of the Ukrainian intangible heritage and architecture as one of its forming aspects should take its place in educational programs.